Analysis of Factors Affecting Air Kerma Area Product Obtained during Uterine Artery Embolization Procedures Using Logistic Regression - Soliman, Khaled; Almutairi, Ahmed; AlHarbi, Murdhi; Almutairi, Khaleel; Almutairi, Turky; Bakkari, Mousa (Indian Journal of Radiology and Imaging, 2021)
Purpose Uterine artery embolization (UAE) is a common interventional radiology procedure used in medicine; the procedure is safe but there is always a concern regarding radiation dose received by the patient. The aim of this study was to use multivariable logistic regression analysis (MLRA) to study a certain number of independent prognostic variables believed to provide an estimate of the likelihood of obtaining a high kerma area product (PKA) at the end of the procedure.Method Radiation dose indices registered by the angiographic system structured dose report, the total fluoroscopy time (FT), the patient’ body mass index (BMI), the number of images taken during the procedures (IMGS), and the performing physician experience (EXPER) were used to drive a logistic regression model (LRM).Results The LRM found was: Logit (PKA) = −6.1525 + 0.0416 (FT) + 0.1028 (IMGS) + 0.1675 (BMI) – 0.1012 (EXPER). The prediction accuracy of the LRM was assessed using receiver operating characteristic (ROC) curve; by calculating the area under the curve (AUC), we found AUC = 0.7896, with optimal ROC point of 0.3261, 0.8036.Conclusion The suggested LRM seems to indicate that patients with higher BMI, have taken longer FT, acquired higher IMGS and the procedure done by a less experienced performing physician is more susceptible to receive a higher PKA at the end. The proposed LRM is useful in predicting the occurrence of higher radiation exposure interventions and can be used in patients’ radiation dose optimization strategies during UAE procedures.
Keywords: air kerma; logistic regression; predictive variables; uterine artery embolization; radiation dose